Assessing the Algerian commercial logistics performance: analytical inquiry - Nacera Arrouche; Chems Eddine Boukhedimi (Менеджмент та підприємництво: тренди розвитку)
The purpose of this paper is to assess the current state of commercial logistics in Algeria, by highlighting the main obstacles facing the growth of exports. Furthermore, it is important to outline the value of logistics and transport infrastructure in the dynamics of a country's foreign trade. In order to achieve these objectives, the research is based on the qualitative method through the exhibition of the previous studies which carried on this subject. Furthermore, the paper employed a quantitative data analysis by the analysis of the logistic performance index between 2012 and 2022.